Circulating levels of inflammatory cytokines (IL-1β and TNF-α), resistance to activated protein C, thrombin and fibrin generation in uncomplicated pregnancies - Ku, De-Hui W.; Arkel, Yale S.; Paidas, Michael P.; Lockwood, Charles J. (Thrombosis and Haemostasis, 2003)
We studied 33 women during normal uneventful pregnancies and with no history of previous adverse pregnancy events for markers of activated coagulation and thrombin activity including prothrombin fragment 1.2(PF1.2), thrombin- antithrombin (TAT), and soluble fibrin polymer (SFP). In addition, we measured potential thrombin generation through the addition of thromboplastin to patient plasma in the presence of a throm-bin-specific chromogenic substrate determined serially over a period of time - Endogenous Thrombin Potential assay (ETP). This assay was performed with plasma treated and untreated with activated protein C (APC). The fibrinolytic system was assessed by measurement of thrombin activatable fibrinolysis inhibitor (TAFI). These findings were correlated with the levels of pro-inflammatory cytokines, interleukine-1β and tumor necrosis factor-α. Our data supports previous reports that indicate that resistance to activated protein C and coagulation activation markers are commonly increased in the later 2/3rds of pregnancy. There are no differences in thrombin generation potential, as determined by the ETP assay without the addition of APC, in the three trimesters. However, the thrombin reserve (TR), the ETP result without APC divided by the ETP result with the addition of APC, is increased above the reference range in the 2nd and 3rd trimesters. Patients with increased TR and resistance to APC had increased levels of TNF-α. Increased proinflammatory cytokines are reportedly associated with changes in the APC system with a decrease in the ability to generate APC. A sub-group of pregnancies with APC resistance had increased levels of TNF-α and may be important in the risk for adverse pregnancy outcomes.
Keywords: ETP; activation markers; pro-inflammatory cytokines; TAFI